2010
DOI: 10.1590/s0004-27302010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dos ácidos graxos n-3 no perfil glicêmico e lipídico, no estresse oxidativo e na capacidade antioxidante total de pacientes com síndrome metabólica

Abstract: OBJETIVO: A síndrome metabólica (SM) é um conjunto de fatores que favorecem o desenvolvimento de doenças cardiovasculares. Estudos prévios demonstram que os ácidos graxos poliinsaturados (PUFAs) podem melhorar alguns desses fatores. O objetivo foi avaliar o efeito do óleo de peixe rico em PUFAs nos perfis glicêmico e lipídico, no estresse oxidativo e na capacidade antioxidante total (TRAP) no plasma em pacientes com SM. SUJEITOS E MÉTODOS: Foi realizado um ensaio clínico em 40 pacientes com SM (20 controles e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 37 publications
2
1
0
2
Order By: Relevance
“…Similar results were found in fish oil (3 g) research, rich in polyunsaturated fatty acids, indicating a reduction of TG in the group that used fish oil when compared to the control group (without substance use). In addition to this indicator, there was an increase in total antioxidant capacity [ 47 ], a fact that was also observed in our study with GB supplementation. The reduction in TG levels observed in the C group is probably due to the introduction in the diet of a greater quantity of fruits and vegetables since all the volunteers were directed to introduce a healthy diet as described in Materials and Methods.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were found in fish oil (3 g) research, rich in polyunsaturated fatty acids, indicating a reduction of TG in the group that used fish oil when compared to the control group (without substance use). In addition to this indicator, there was an increase in total antioxidant capacity [ 47 ], a fact that was also observed in our study with GB supplementation. The reduction in TG levels observed in the C group is probably due to the introduction in the diet of a greater quantity of fruits and vegetables since all the volunteers were directed to introduce a healthy diet as described in Materials and Methods.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, the total cholesterol and TG of the rats fed diets enriched with Amazon fish decreased and the HDL of rats fed diets enriched with mapará and tambaqui increased -these fish contain omega-6 and omega-3 fatty acids. The plasma glucose levels did not differ significantly from those of the control group, which was also observed by Simão et al 31 and Wilkson et al 32 while supplementing a human diet with fish oil. Mortiz et al 33 stated that rats fed with chow enriched with fish oil tended to have lower blood glucose, total cholesterol, and LDL-c and higher TG than the control group.…”
Section: Discussionsupporting
confidence: 82%
“…demonstrated that the n-3 LC-PUFA did not increase the biomarkers of oxidative stress, such as 8-iso-PGF (2alpha) and 15-keto-dihydro PGF (2alpha) (9). DNA damage, such as that by 7, 8-dihydro-8-oxo-2’-deoxyguanosine in mildly hypertriacylglycerolemic patients (33), indicated that n-3 LC-PUFA-enriched products do not cause additional oxidative DNA damage as shown by the excretion of 7, 8-dihydro-8-oxo-2’-deoxyguanosine.…”
Section: Discussionmentioning
confidence: 99%